Pengembangan Media Komik Berbasis Etnosains Materi Usaha dan Pelestarian Lingkungan Kelas V Sekolah Dasar - Hasna Fauziah; Sri Estu Winahyu; Esti Untari (Universitas Negeri Malang, 2023)
The research and development carried out aims to create comic learning media based on ethnoscience that is valid based on media and material experts, practical based on teachers, and creates interest for students. The research applies ADDIE modeling which consists of 5 stages: 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluation. Instruments in research use questionnaires, then analyze them using qualitative and quantitative data analysis. The results of the development are in the form of ethnoscience-based comic learning media products with science content, especially business materials and environmental conservation. This media is in the form of printed books. The material is presented through a story with interesting color images. The average score of the product evaluated by media experts is 96 percent, material experts 100 percent, and teachers as end users 92.5 percent. The validity and suitability of the product for use, as indicated by the validation findings, does not include any changes to the product. Small-scale testing results in a 90 percent attractiveness score, while large-scale testing results in a 96 percent score. Based on the results of that percentage, it concludes that ethnoscience-based comic learning media is valid based on media and material experts, practical based on teachers as users, and creates interest for fifth grade elementary school students. Penelitian dan pengembangan yang dilaksanakan bertujuan untuk menciptakan media pembelajaran komik berbasiskan etnosains yang valid berdasarkan ahli media dan materi, praktis berdasarkan guru, dan menciptakan ketertarikan untuk siswa. Riset menerapkan pemodelan ADDIE yang terdiri dari 5 tahap: 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluation. Instrumen dalam riset mempergunakan angket, kemudian dianalisisnya mempergunakan menganalisis data kualitatif maupun kuantitatif. Hasil pengembangan berupa produk media pembelajaran komik berbasis etnosains dengan muatan IPA khususnya materi usaha dan pelestarian lingkungan. Media ini berupa buku cetak. Materi disajikan melalui cerita dengan gambar berwarna yang menarik. Skor rerata produk yang dievaluasi oleh ahli media adalah 96%, ahli materi 100%, dan guru sebagai pengguna akhir 92,5%. Validitas dan kesesuaian produk untuk digunakan, seperti yang ditunjukkan oleh temuan validasi, tidak termasuk perubahan apa pun pada produk. Pengujian skala kecil menghasilkan skor daya tarik 90%, sedangkan pengujian skala besar menghasilkan skor 96%. Didasarkan atas hasil persentase itu, menyimpulkan yakni media pembelajaran komik berbasis etnosains valid berdasarkan ahli media dan materi, praktis berdasarkan guru sebagai pengguna, dan menciptakan ketertarikan untuk siswa kelas V SD.